(untitled) (Brazilian Journal of Pharmaceutical Sciences, 2017)
This study aimed to investigate the effect of peracetic acid (PAA, 0.5%) on adherent cells of three strains of Listeria monocytogenes strains belonging to serotypes 4b and 1/2b that had been previously isolated from the environment of a Brazilian cheese plant. The assays were conducted using polystyrene microplates and stainless steel coupons and the adhered cells were treated with PAA for 60, 120 and 180 s. On stainless steel, biofilms were partially inactivated by PAA after 60 s and almost 100% of the cells were damaged within 180 s using epifluorescence microscopy with LIVE/DEAD® staining. On polystyrene microplates, PAA decreased (P